CONCEPTUAL REINTERPRETATION OF THE ROLE OF THE SHARIA SUPERVISORY BOARD IN REALIZING COMPLIANCE IN THE ERA OF DIGITAL DISRUPTION - ismail, hilmayani; Arqam (IAIN Parepare, 2025)
Digital transformation has significantly changed the landscape of the Islamic financial industry, presenting new challenges and opportunities for the Sharia Supervisory Board (SSB). This study aims to conceptually reinterpret the role of the SSB in ensuring compliance with sharia principles amidst digital disruption. Using a qualitative literature study approach, this article analyzes findings from various scientific journals, regulations, and related fatwas. The results of the study indicate that the role of the SSB, which has so far been normative and administrative, is not sufficient to address the complexity of digital innovation. Therefore, a new approach is needed that positions the SSB as a strategic actor in technology-based supervision, information system integration, and digital competency development. Synergy between the SSB, regulators, academics, and industry players is key to building an adaptive and responsive sharia compliance system in the digital era.